Genome-wide analysis and environmental response profiling of phosphate-induced-1 family genes in rice (Oryza sativa). Issue 1 (1st January 2019) - Quan, Changqian; Bai, Zhigang; Zheng, Shiwei; Zhou, Jingming; Yu, Qiang; Xu, Zhengjun; Gao, Xiaoling; Li, Lihua; Zhu, Jianqing; Jia, Xiaomei; Chen, Rongjun
Abstract: Phosphate-induced-1 (PHI-1) and phosphate-induced-1-like family genes respond to plant hormones such as abscisic acid (ABA), BR (brassinosteroid) and ethylene. To date, very few researches have been done on abiotic stress for PHI-1 genes. In this work, we report 12 rice PHI-1 genes through genome-wide analysis. The 12 OsPHI-1 genes were tandemly arranged into two clusters and nine conserved motifs were found among their amino acid sequences. Microarray data indicated that all the OsPHI-1 genes exhibited identical expression level but different expression patterns: most OsPHI-1 genes were expressed intensively in panicle development and responded to IAA and BAP treatments; several OsPHI-1 genes responded to trans-zeatin (tZ) and dimethyl sulfoxide (DMSO) treatments; 11 OsPHI-1 genes showed response to abiotic stress. Furthermore, the promoter region analysis showed that all the OsPHI-1 genes contained cis- regulatory elements responding to abiotic stresses. Our study will be helpful to further investigate the biological functions of PHI-1 genes in rice.